O Estado Brasileiro contemporâneo: Liberalização econômica, política e sociedade nos governos FHC e Lula - Sallum, Brasilio; Goulart, Jefferson O. [UNESP] (FapUNIFESP (SciELO), 2016)
The article identifies the features of the contemporary form of the Brazilian state - in force since 1995 - focusing its relations with the economic sphere and its policies against social inequality. It characterizes the ideas that guided the governing elites, the way the Brazilian foreign policy was redefined after the Cold War, the economic and social policies between 1995 and 2010. The central hypothesis is that there is a new form of State in Brazil since 1995 and that the variations between the different governments are part of the same story. The article opposes to the current characterization of the FHC and Lula governments as having followed a neoliberal policy. For this, it seeks to identify the policy that guided the two periods of government. It shows that it was liberalizing but moderate in regard to state intervention in the economy - merging policies guided by neoliberal and liberal-developmentalist ideas. Although there is enough continuity in government policies regarding the economy, the article attempts to show that the Lula period had a very important role in the stabilization of the state and even in the capitalist order. Indeed, the incorporation of union leaders, social movements and, in general, leftists to the State management, the extension of social protection to the poor and miserable and the creation of channels to facilitate the upward mobility of lower middle class strengthened the accession to the capitalist order and political stability, complementing the stabilizing effects of democratic rules and currency stability already recognized in the literature.
The Brazilian contemporaneous state: Economics liberalization, politics and society in the governments Lula and FHC
Keywords: Development; Liberalization; Neoliberalism; Social policy; State